Measurement of conspirativistic mentality: primary psychometric verification of diagnostic methodology - Влада И. Пищик (Российский психологический журнал, 2022)
Introduction. The study of the specific features of the prevalence of belief in various conspiracies is an urgent problem of the crisis of our time. The available methods are mainly focused on the types of belief in conspiracies, but there is little attention given to holistic approach. We are the first to demonstrate on the Russian sample the developed new valid and reliable tools for identifying the features of the conspirativistic mentality of modern youth. Methods. The construct of the methodology is based on the stages of perception of belief in conspiracies and the allocation of significant attitudes – resistance to conspiracies, willingness to accept conspiracies on faith, the desire to look for the causes of conspiracies and evaluate the consequences and results of their impact on life. The methodological tools are presented by the author's methodology "Measurement of conspirativistic mentality", tested on 300 male and female respondents. The construct of the methodology has a two–factor structure, on one pole - readiness–stability in relation to the conspiracy, on the other - seeking-productive types. Results. Psychometric testing of the technique showed that men and women have different manifestations of a conspiratorial mentality. Men have a higher belief in conspiracies. Ready and productive types are closer to the zone of tradition, and stable and searching types are more in the zone of innovation. The constructive validity of the methodology was confirmed, and a high α-Kronbach index was obtained, which indicates the internal consistency of the methodology. Discussion. The data obtained are combined with existing studies of certain aspects of conspirativism. We found confirmation of the following ideas: the sexual difference of the conspiratorial mentality, its personal identity, the specifics of orientation, connection with anxiety and basic fears. Conclusion. Preliminary psychometric verification of the methodology on a representative sample demonstrates its reliability and validity. The Further work will be aimed at modifying the methodology and comparing age groups.